Handbook of research on comparative human resource management - Brewster, Chris; Mayrhofer, Wolfgang; Edward Elgar Publishing (Cheltenham, U.K. : Edward Elgar, 2012)
This unique and path-breaking Handbook explores the issue of comparative Human Resource Management (HRM) and challenges the notion that there can be a'one best way' to manage HRM.
Includes bibliographical references and index.
Keywords: Personnel management -- Research; Industrial management -- Research